Boosted hydrogen evolution from α-MoC1-x-MoP/C heterostructures. (20th February 2020) - Liu, Tianying; Zhang, Xiangyong; Guo, Ting; Wu, Zhuangzhi; Wang, Dezhi
Abstract: To explore highly effective catalysts with low cost and earth abundant for the hydrogen evolution reaction (HER), in this work, a novel electrocatalyst of alpha-molybdenum carbide and molybdenum phosphide heterostructure embedded in N-doped carbon (α-MoC1-x -MoP/C) is synthesized via facile simultaneous carbonization and phosphorization strategy for the first time, which exhibits an excellent hydrogen evolution activity with a Tafel slope of 57 mV dec −1 in an acidic media. A strong electronic interaction between α-MoC1-x and MoP in the interfaces is verified experimentally and theoretically, which contributes to a mild free energy of H adsorption and smaller charge transfer resistance, resulting in an improved HER activity.